2019
DOI: 10.1021/acs.jafc.8b06591
|View full text |Cite
|
Sign up to set email alerts
|

Detailed Phytochemical Characterization of Bergamot Polyphenolic Fraction (BPF) by UPLC-DAD-MS and LC-NMR

Abstract: Bergamot (Citrus bergamia) is cultivated in Southern Italy almost exclusively to produce the prized essential oil, a top note in several perfumes. The juice of bergamot, until recently poorly studied, is the object of a growing scientific interest due to its claimed activity to treat metabolic syndrome. The aim of this investigation was a detailed characterization of bergamot juice polyphenolic fraction (BPF) based on a UPLC-DAD-MS analysis complemented by preparative chromatographic separations, followed by N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 33 publications
1
24
1
Order By: Relevance
“…Its UV spectrum was characterized by 2 strong absorptions at 253 e 347 nm, while the full mass spectrum showed a deprotonated molecule [M -H] − at m/z 397, which generated product ions in MS/MS experiments at m/z 235 [M -H -162] − and 191 [M -H -206] − due to the loss of quinic and synapoyl acids, respectively. On the contrary, the limonoid limonin glucoside, reported by Da Pozzo et al [8], was not herein detected, while the aglycones nomilinic acid (22) and limonin (23) were observed as previously reported [7,9]. In addition, a higher number of phenolics were identified considering a very recent study on C. bergamia juice chemical content [9].…”
Section: Resultscontrasting
confidence: 48%
See 1 more Smart Citation
“…Its UV spectrum was characterized by 2 strong absorptions at 253 e 347 nm, while the full mass spectrum showed a deprotonated molecule [M -H] − at m/z 397, which generated product ions in MS/MS experiments at m/z 235 [M -H -162] − and 191 [M -H -206] − due to the loss of quinic and synapoyl acids, respectively. On the contrary, the limonoid limonin glucoside, reported by Da Pozzo et al [8], was not herein detected, while the aglycones nomilinic acid (22) and limonin (23) were observed as previously reported [7,9]. In addition, a higher number of phenolics were identified considering a very recent study on C. bergamia juice chemical content [9].…”
Section: Resultscontrasting
confidence: 48%
“…Protective Effects of Bergamot (Citrus bergamia Risso & Poiteau) Juice in Rats Fed with High-Fat Diet highlighted the richness of bergamot juice in health-promoting compounds, encouraging its cultivation and marketing. Several chemical investigations have reported bergamot juice as a rich source of flavones and flavanones, with naringin, neohesperidin, and neoeriocitrin being the most represented constituents [6][7][8][9]. The great nutraceutical interest of bergamot juice is still growing, mainly for the pharmacological potential of its health-promoting substances.…”
Section: Introductionmentioning
confidence: 99%
“…The general properties of these citrus herbs are depicted in Supporting Information Figure S1 and Table S1. Phytochemical studies showed that the major flavanones and PMFs from citrus herbs (e.g., narirutin, Article Related Abbreviations: ABTS, 2,2′-azino-bis (3-ethylbenzothiazoline-6-sulphonic acid); CAT, catalase; CP, Chenpi; DDH, Daidaihua; DPPH, 1,1-diphenyl-2-picrylhydrazyl; FRAP, ferric reducing antioxidant power; FS, Foshou; GSH, glutathione peroxidase; HJH, Huajuhong; JH, Juhe; JL, Juluo; MFDPH, medicine-food dual-purpose herb; QP, Qingpi; ROS, reactive oxygen species; SOD, superoxide dismutase; XY, Xiangyuan; ZQ, Zhiqiao; ZS, Zhishi hesperidin, neohesperidin, eriocitrin, neoeriocitrin didymin, nobiletin, and tangeretin) were the major flavonoids that have been affirmed to be therapeutic or nutraceutical with many biological activities [11,12], such as antioxidant [5,13,14], anti-diabetic [15], antibacterial [16], anti-inflammatory [13,17], and antitumor [18] effects. Investigations focused on gastrointestinal regulation and respiratory diseases were reported extensively, but few reports on phytochemicals differentiation and antioxidant ability among citrus herbs, which was one of the most important characteristics for foods functions.…”
Section: Introductionmentioning
confidence: 99%
“…A lecithin food-grade delivery system (Phytosome®) containing the Bergamot Polyphenolic Fraction (BPF) from Citrus Bergamia Risso et Poiteau from Calabria was developed by Indena SpA to ameliorate the oral absorption of avonoids. The structural phytochemical composition of bergamot was deeply analysed by HPLC-DAD-MS and LC-NMR [8], and a recent clinical trial in individuals with type 2 diabetes mellitus and hyperlipaemia showed a reduction of cardiovascular risk by modulating total cholesterol (tChol), low-density Lipoproteins (LDL), triglycerides (TG), high-density Lipoproteins (HDL) and blood glucose after just 30-day supplementation [9].…”
Section: Introductionmentioning
confidence: 99%